Red in tooth and claw: A review of animal antagonistic roles in movies. Issue 3 (28th February 2022) - Chiacchio, Michele; Pigoni, Alessandro
Abstract: Although cinema narrative represents a fundamental communication tool in framing public opinion, whether a negative representation of certain species in the context of animal‐horror movies might increase the attitudinal hostilities towards them remains an aspect of wildlife perception that is poorly studied. Here, we reviewed online sources from the last 70 years to describe the negative representation of animal roles in horror and disaster movies. Specifically, we described species diversity, how the animal was depicted, the cause for its aggressive behaviour and how it came in contact with the human characters. By means of principal coordinate analysis (PCoA), we also highlighted three main typologies of animal‐horror movies. The dataset consisted of 263 titles produced world‐wide from 1950 to 2019. The results showed that animal representation is transversal yet uneven, with five species groups out of 18 appearing in more than half of the movies. There were significant associations between species, their representation and the different kinds of movies they appeared in, with some species groups appearing more commonly in certain types of film plots rather than others. Together, the results suggested that both the themes and topics of animal‐horror movies were often the result of a combination of factors, including fashion‐driven audience interests, societal and political concerns, and technological availability at the time of production. Whether this repeated and variegated representation can increase attitudinal hostility remains however unclear. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.